The favorable alleles of AKIRIN2:c.*188G>A, EDG1:c.-312A>G and TTN:g.231054C>T as candidate markers for high-marbling are very low in Bali cattle - SAIFUL ANWAR; ARI SULISTYO WULANDARI; WIDYA PINTAKA BAYU PUTRA; SYAHRUDDIN SAID (Society for Indonesian Biodiversity, 2019)
Abstract. Anwar S, Wulandari AS, Putra WPB, Said S. 2019. The favorable alleles of AKIRIN2:c.*188G>A, EDG1:c.-312A>G and TTN:g.231054C>T as candidate markers for high-marbling are very low in Bali cattle. Biodiversitas 20: 965-970. Marbling is one of primary factors influencing the palatability of beef. The AKIRIN2, EDG1 and TTN genes are considered as the three candidate genes responsible for high-marbling in beef cattle. This study aimed to investigate the genetic polymorphism of the SNPs of AKIRIN2:c.*188G>A, EDG1:c.-312A>G and TTN g.231054C>T in Bali cattle. A total of 125 DNA samples of Bali cattle were genotyped for AKIRIN2 and TTN gene and 82 DNA samples for EDG1 gene using PCR-RFLP method. In the present study, it was found that the A allele of AKIRIN2:c.*188G>A, the G allele of EDG1:c.-312A>G and the T allele of TTN g.231054C>T that considered as the favorable alleles were found to be very low in Bali cattle (0.004, 0.000, and 0.004, respectively). This results indicated that the polymorphism of AKIRIN2:c.*188G>A, EDG1:c.-312A>G and TTN g.231054C>T were very low and can be considered as monomorphic in Bali cattle. These findings suggested that Bali cattle may not genetically potential as a high-marbling cattle breed. However, the other specific genes for high-marbling still needs to be investigated in Bali cattle.